Nineteen minutes : a novel - Picoult, Jodi. (New York : Atria Books, 2007)
The daughter of a judge in a New Hampshire school shooting case witnessed the events, but cannot remember the last several minutes of the attack
Keywords: Bullying -- Fiction; Fiction -- Contemporary Women